Geomorphological evolution and relative chronology of terrace levels adjacent to the Chubut river mouth to the Atlantic (Chubut Province) - González Díaz, E.F. (2011)
An ancient alluvial fan and its subsequent evolution are described. Ancient alluvial fan accumulations have been interpreted as the northern continuation of the rodados patagónicos of the Montemayor Plateau, a proposal that is contested. The methodological recognition of the ancient alluvial fan and its genetic and temporary distinction, were made from geomorphologic analysis and altimetric evaluation. Time assignment is a problem not yet solved. The methodology led to three different geomorphic systems or levels related to successive episodes of aggradation and erosion, with increasing lower positions, which coincide with a complex paleodrainage ancient alluvial fan. its successive developments are linked to proposed proto-rivers Chubut 1, 2, 3 and to a Simpson paleo-valley. Despite the mentioned limitations, we propose that the evolutionary model of ancient alluvial fan responds to a structure of cut and fill which is supported by the poly-formational composition of an ancient alluvial fan, and a gradual southward migration of the paleo-drainage. Based on geomorphologic analysis and altimetric distinction an upper level, composed of the remains of three plains (Pa, Pm and Pb), a middle level with two terraces (T1 and T2) and a complex lower level and five terraces (T3, T4, T5 T6 and T7) were recognized. Relict evidences of paleo-drainages are proposed based on the Estancia Paz and Don Morgan-Saraza paleo-valleys in the upper level. The age of the ancient alluvial fan based on the geomorphic evolution of the study area is tentatively assigned to an uncertain period between the late Pleistocene and late Sangamon interglacial at the end of the last glaciation.